Obstacles In Mathematics Learning And Mathematics Teaching Strategies: A Qualitative Study On The Experiences Of Prospective Teachers - Salsabillah, Chalisa; Wagyina, Ana; Wahyunengsih; Rohmah, Mushlihah (Trigonometri: Jurnal Matematika, 2026)
This study was conducted with the primary aim of identifying the main barriers in mathematics learning and determining effective teaching strategies to overcome them. Employing a qualitative research approach, data were collected from twenty respondents comprising educators and stakeholders in the field of education. To ensure a rigorous interpretation of these perspectives, the data underwent thematic analysis, allowing for the systematic categorization of participant responses into core pedagogical themes. The findings indicate that the most prominent barriers are low student motivation and lack of parental support, with 90% of participants identifying these as critical challenges affecting student learning outcomes. These factors contribute significantly to disengagement and reduced academic performance in mathematics. On the other hand, the study also reveals encouraging trends. All respondents (100%) expressed a positive attitude toward collaborative lesson planning, emphasizing that working together in designing learning activities enhances both teacher creativity and instructional effectiveness. A substantial majority (86.67%) also acknowledged the potential of technology integration in making mathematics more accessible and engaging. Furthermore, there was unanimous agreement on the importance of ongoing professional development (100%) as a vital component for teacher growth and improved pedagogy. This research offers a novel contribution by bridging the gap between stakeholder-identified barriers and specific collaborative interventions, providing a localized framework for teacher-led reform. Taken together, these findings highlight the need for comprehensive educational interventions that include strengthening teacher capacities, fostering home-school collaboration, integrating digital tools in classrooms, and promoting continuous teacher training. Such efforts are essential to improve students' understanding, interest, and achievements in mathematics.